Relapsing polychondritis (clinical observations) - Е. N. Skryabina; О. L. Aleksandrova; I. А. Romanova; А. Р. Rebrov; N. М. Nikitina (Научно-практическая ревматология)
Relapsing polychondritis (RPC) is an autoimmune disease manifested by both repeated attacks and a persistent inflammatory process with progressive destruction of cartilaginous structures, in particular, chondritis of the ears, nose, larynx, bronchi, and joints. RPC is a rare disease (about 1000 cases have been described worldwide). Diagnosis of RPC and the choice of treatment tactics are very difficult, which is associated with the rarity of the pathology, undulating, unpredictable course, and the lack of specific laboratory markers.The clinical observations presented in the article confirm the complexity of diagnosing RPC. Before the disease was verified, both patients repeatedly consulted different specialists: the first patient was diagnosed 3 months after the onset of characteristic symptoms of RPC, and the second patient – 1.5 years later. Late diagnosis and the lack of a unified approach to treatment were the reason for the development of prognostically unfavorable lesions in the second patient – chondritis and perichondritis of the larynx.